Measuring the Impact of Changes in Production Incentives on theCompetitiveness of the Film and Television Industries: A Post-Strike Case Study in the United States and Canada - Tumiar Berthalina Simatupang, S.I.Kom, M.I.Kom, Tumiar Berthalina Simatupang, S.I.Kom, M.I.Kom (Akademi Komunikasi SAE Indonesia, 2025)
Particularly after significant strikes in Hollywood in 2023 and 2024, the film and television sectors are currently facing significant challenges. This paper aims to explore how variations in production incentives affect the competitiveness of the film and television sector in the US and Canada. Through a qualitative approach and literature analysis, the study revealed that more competitive incentive policies in Canada could attract more film investment than states in the United States with less appealing regulations. Additionally, the study illustrates how the strikes have impacted investment decisions across sectors and disrupted production, thereby creating uncertainty that hampers the growth of the filmand television industries. This study advocates for policy changes to promote industry sustainability by emphasizing the importance of adaptive incentive strategies that respond to evolving global market dynamics. The findings should provide lawmakers and industry stakeholders with valuable insights and recommendations for enhancingcompetitiveness in the film and television sectors.